TINJAUAN HUKUM TERHADAP PEMBERIAN PINJAMAN MODAL USAHA OLEH PERBANKAN KEPADA PELAKU USAHA MIKRO, KECIL, DAN MENENGAH DI LINGKUNGAN SITUS KUTAI LAMA - Wahyuni Safitri; Rustiana; Nainuri Suhadi (Yuriska: Jurnal Ilmiah Hukum, 2024)
This research aims to analyze and determine the role of banking in Providing business capital for MSMEs in the Kutai Lama area and analyze banking efforts in overcoming obstacles faced by perpetrators MSMEs in the Kutai Lama site environment in providing business capital loans.The method used in this research is a qualitative method, with normative juridical approach.The research results show that banking has a very big role in helping MSMEs develop business through providing business capital for MSME actors, especially those in wealth in the old Kutai site environment. There are two important roles for banking in helping MSMEs in developing their business both before roviding business capital and After providing business capital, namely first, carrying out an powerment program MSMEs before providing business capital loans. Second, do the program coaching and supervision of MSMEs after providing business capital loans.Furthermore, there are banking efforts to overcome the obstacles faced by MSME actors in the Kutai Lama site environment in providing business capital loans namely by providing outreach regarding financing for MSMEs by parties banking, Providing training and education for MSME players so they can develop business income, and provide credit restructuring for MSME players who have had a history of bad credit.